Pemetaan Jaringan Jalan di Universitas Palangka Raya - Paschalia Retnoningtyas Surbakti; Desi Riani; Murniati (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2023)
Roads have an important role in the realization of balanced inter-regional development for equitabledevelopment. Spatial mapping of the area and road network at the University of Palangka Raya which iscurrently undergoing infrastructure development and development aims to find out the area and coordinatesof the boundaries of the University of Palangka Raya. This study also aims to calculate the total length ofexisting roads in the University of Palangka Raya area. This mapping uses the photogrammetric method. Thetool used is the Unmanned Aerial Vehicle (UAV) or the DJI Mavic 2 Pro Drone with Benchmark control pointsand Ground Control Point (GCP). Aerial photography was carried out on 14-21 October 2022 at the Universityof Palangka Raya which was divided into 10 flyways and the number of photos was 7,395. The flying altitudeof the drone is 100 m with 75% overlap/sidelap and 90 camera angle. Retrieval of Benchmark coordinates andGround Control Point (GCP) data using the Geodetic GPS tool on October 14, 2022 with a total of 2Benchmarks and 33 GCP points. Then proceed with the digitization process based on street names and areasper faculty at University of Palangka Raya. From the results of this study it was found that the University ofPalangka Raya has 11 roads that connect faculties and buildings to one another. The total length of existingroads is 17,391,662. The longest road is Hendrik Timang street with a length of 6,557.632 m and the shortestroad is Damang Salilah street with a length of 310.117 m.